The teachers beliefs about the english language leaners - Mejía Cruz, Sonia Arely; Meléndez Arita, Donna Mariela; Ramírez Mejía, Mauricio Enrique (2024)
The teacher’s beliefs about language learners greatly influence the way how the teaching –learning process is achieved. Beliefs are culturally bound and, since they are formed early in life, they tend to be resistant to change. This constitutes the reason why the following essay will, above all, focus on the importance or the role of the teachers’ beliefs about the English language learners that they bring into the classroom. By going through this awareness, teachers will be able to examine why they do what they do and, perhaps, to choose to think about things differently. Part of the content of this essay comes from the contribution of the beliefs demonstrated by some teachers at the Foreign Language Department trough five years of academic activity which has allowed the recognition of their thoughts and ideas about the teaching activity. In addition, different bibliography has been taken into account to get a variety of information, opinions and thoughts that teachers have about the English language learners. This bibliographical research paper contains an introductory section to provide a brief overview on what it is about continuing with the stating of the general and specific objectives aimed to achieve. A justification is also included to present the intentions why this work has been conducted and who will be benefited following with the body of the work. The methodology that was used is also explained and some recommendations are offered. At the end, there are the references for the bibliography that was consulted along with the annexes including the detailed steps performed to achieve the final paper work.